Tower building model based on sustainable social development and its effects on the preservation of Tehran\'s urban environment - Valiollah ghasemi; afshin ghorbani param (تحقیقات کاربردی علوم جغرافیایی)
Industrialization and modernization have had a significant impact on various aspects of society including architecture, urban planning, environment, climate, and geography. This impact is evident in phenomena such as the construction of high rise buildings, climate inversion, and environmental degradation. Many of the problems observed in recent decades can be attributed to population growth, migration, and changing needs of citizens. As a result, city managers and architects face significant challenges. The main objective of this article is to conduct a theoretical study on the use of residential towers, with a particular focus on sustainable social development and its implications for environmental protection in Tehran. This research adopts a descriptive-analytical approach and has both applied and theoretical purposes. It is also part of a survey that employs both quantitative and qualitative research methods. The sample size for this study was 384 participants, and data were collected using questionnaires. The data analysis was conducted using SPSS software. The most significant finding of this research is that population growth has fueled the construction of tall buildings, which in turn has contributed to issues such as excessive consumption of natural resources and fossil fuels, destruction of natural habitats, decline in social interactions, climate change, increased traffic congestion, and heightened air pollution. These issues have become a complex and seemingly insurmountable crisis.